Correlation Relationship of Interferons, Cytokines with Biochemical Mediators of Inflammation in The Blood in The Association of Covid-19 and Type 2 Diabetes (Texas Journal of Medical Science, 2023)
The study included 103 patients hospitalized for SARS-CoV-2 pneumonia at the Bukhara Regional Infectious Diseases Hospital, which was reorganized into the Covid Center. Immunological studies of the blood of sick children were carried out in the laboratory of immunomorphology of the Institute of Human Immunology and Genomics of the Academy of Sciences of the Republic of Uzbekistan. The indicators of interferon (INF-a, IFN-γ), cytokines (IL4, IL18) and biochemical tests in the blood were studied.